HUMAN RESOURCE ORIENTATION AND PLACEMENT AT MTsN 2 BOGOR - Dewi Septiani (Al Arsy: Journal of Education, Management and Islamic Thought, 2026)
In the era of globalization, the quality of human resources has become a crucial factor in determining the competitiveness of educational institutions. This study aims to analyze the implementation of human resource orientation and placement at MTsN 2 Bogor. The research employed a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation, involving selected participants using purposive sampling. Data analysis was conducted using inductive techniques, including data reduction, data presentation, and conclusion drawing. The findings reveal that the orientation process at MTsN 2 Bogor is carried out systematically, starting from needs analysis, recruitment planning, selection, and continuing to orientation prior to job placement. Orientation serves not only as an introduction process but also as a strategic effort to accelerate the adaptation of new teaching staff to the work environment, responsibilities, and organizational culture. A participatory and communicative approach in orientation helps reduce initial anxiety, improve work readiness, and support the development of professional character as well as the internalization of Islamic values. Furthermore, the placement of teaching and educational staff is conducted based on the principle of the right man in the right place, ensuring alignment between competencies, educational background, experience, and institutional needs. Placement is also dynamic, involving transfer mechanisms to optimize staff performance and meet organizational demands. Appropriate placement has been shown to enhance productivity, motivation, and overall performance of educators. In conclusion, orientation and placement play a significant role in improving the quality of human resources at MTsN 2 Bogor. Both processes contribute to creating a conducive work environment, strengthening professionalism, and supporting the achievement of educational goals effectively.